Benchmarking Institutions of Applied Sciences, Engineering and Technology in Sub-Saharan Africa : Benchmarking Results - World Bank (World Bank, Washington, DC, 2016)
In this benchmarking report, a comprehensive benchmarking analysis of the participating Sub-Saharan African universities is conducted in terms of the key indicators identified and constructed for the purpose of assessing institutional performance and health. While university benchmarking is a relatively new approach for most Sub-Saharan African universities that are participating for the first time in this process, it has been used as a diagnosis and planning tool by many universities to understand and track their own performance over time and against their local and global peers. For Sub-Saharan African universities, there is a need to take stock of outstanding achievements in the past, catch up with local peers in the near future, and set long-term targets on the road to becoming a top-performing university in the world. It is expected that this benchmarking analysis will serve as the basis for understanding the relative performance of Sub-Saharan African universities as well as a catalyst for these universities to take appropriate quality improvement measures and carry out effective strategic planning. For this phase of the Partnership for Skills in Applied Sciences, Engineering and Technology (PASET) Regional Benchmarking Initiative, 28 out of the 48 Sub-Saharan African universities that signed up have participated and attempted the benchmarking exercise to different extents.